2017
DOI: 10.1111/bcp.13389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of caffeine disposition following administration by oral solution (energy drink) and inspired powder (AeroShot) in human subjects

Abstract: Inspiration of caffeine as a fine powder using the AeroShot device produces a similar caffeine profile and effects compared to administration of an oral solution (energy drink).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Several studies have also shown that the form of caffeine or its vehicle for entry into the body can modify the pharmacokinetics [ 58 , 81 , 119 , 122 ]. One small trial ( n = 3) evaluated T max for a variety of beverages that all included 160 mg of caffeine but in different volumes of solution, and reported that T max occurs at 0.5, 0.5, and 2 h for coffee, tea and cola, respectively [ 135 ].…”
Section: Caffeine Pharmacokineticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have also shown that the form of caffeine or its vehicle for entry into the body can modify the pharmacokinetics [ 58 , 81 , 119 , 122 ]. One small trial ( n = 3) evaluated T max for a variety of beverages that all included 160 mg of caffeine but in different volumes of solution, and reported that T max occurs at 0.5, 0.5, and 2 h for coffee, tea and cola, respectively [ 135 ].…”
Section: Caffeine Pharmacokineticsmentioning
confidence: 99%
“…Finally, there is a growing prevalence of caffeinated nasal and mouth aerosols administered directly in the mouth, under the tongue or inspired may affect the brain more quickly through several proposed mechanisms [ 5 ], although there are only a few studies to date to support this claim. The administration of caffeine via aerosol into the oral cavity appears to produce a caffeine pharmacokinetic profile comparable to the administration of a caffeinated beverage [ 81 ]. Nasal and mouth aerosols will be discussed further in another section.…”
Section: Caffeine Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations of caffeine were slightly suprapharmacologic to mimic excessive energy drink consumption. Plasma peak concentrations of caffeine after consumption of one serving energy drink with 100 mg caffeine dose is 1790 ng/ml, 16 which equals approximately 9.2 µM. However, far higher concentrations have been calculated for young adolescents consuming energy drinks using a Monte Carlo simulation 17 .…”
Section: Methodsmentioning
confidence: 99%